2018
DOI: 10.1007/s11252-018-0822-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plant type on green roof rainfall retention

Abstract: Green roofs can mitigate the flood risk by reducing the volume of runoff through direct interception and subsequent evapotranspiration (ET), but the planting choices can influence the extent of this service. Glasshouse experiments were carried out in spring/ summer using simulated rainfall to compare the rainfall retention capacity of three physiologically active broadleaf species (Heuchera micrantha, Salvia officinalis and Stachys byzantina), which have previously shown to provide improved rooftop cooling, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Although sedums are the most common plant type used on extensive green roofs, there is much interest in vetting plant choices for improved retention. A study comparing three broadleaf species to the industry standard sedum found that two of the three species ( Salvia and Stachys ) demonstrated the greatest retention due to high ET rates between rainfall events (Kemp, Hadley, & Blanusa, 2019). Canopy interception, which was greatest for the sedum, was found to be a statistically significant factor in retention but was less important than ET and overall substrate water storage.…”
Section: Green Roofsmentioning
confidence: 99%
“…Although sedums are the most common plant type used on extensive green roofs, there is much interest in vetting plant choices for improved retention. A study comparing three broadleaf species to the industry standard sedum found that two of the three species ( Salvia and Stachys ) demonstrated the greatest retention due to high ET rates between rainfall events (Kemp, Hadley, & Blanusa, 2019). Canopy interception, which was greatest for the sedum, was found to be a statistically significant factor in retention but was less important than ET and overall substrate water storage.…”
Section: Green Roofsmentioning
confidence: 99%
“…For example, Jahanfer et al [14] reported peak flow reductions of 58% for "large rainfall events" but large was only defined as depths greater than 10 mm (0.4 in). Kemp et al [15] found vegetative canopies retained 2-17% of rainfall, but for a rainfall depth of only 9.3 mm (0.37 in). This pattern of analyzing smaller storms is very clearly shown by Stovin et al [11] who created detention design charts that show approximations of both peak discharge reduction and runoff delay across a range of rainfall depths.…”
Section: Introductionmentioning
confidence: 99%
“…Other experimental work on green roofs has focused on the plant ecology [8,9] with the aim of greater climatic resilience and possible additional benefits to storm water performance in terms of evapotranspirative efficiency. A final aspect of experimental research is the determination of the growth substrate material composition on detention and retention performance.…”
Section: Introductionmentioning
confidence: 99%